Discretionary Administrative Acts of Territorial Planning and Urban Development Zoning of Municipal Entities - S. S. Kustov (Сибирское юридическое обозрение, 2024)
The paper analyzes the legal regulation of the limits of public authority discretion in territorial planning and urban development zoning of municipal entities, defines the limits of judicial control over bills issued by the relevant authorities. Due to comparative legal method we determine that the common feature for Great Britain, Germany and Russia is rather a broad discretion of authorized bodies in doctrine and practice as for planning, which, however, does not exclude control over issued planning acts. In Russia the powers of the bodies regarding preparation and approval of the documents of territorial planning and urban zoning of municipal entities are of discretionary nature. When issuing such acts, the body exercises the freedom of discretion, resulting from the lack and impossibility to define all legal conditions to adopt planning acts. It is noted that the decisions of public authorities, which enact these documents are the variation of discretional planning acts. In comparison to the practice of the Supreme Court of Russia and the courts of general jurisdiction, the local governing body has a broader discretion in regards of the discussed issues. Discretionary nature of such acts does not exclude evaluation of the limits of body’s discretion. The paper concludes that the restrictions of the directorate of the body, while issuing acts of territorial planning and urban development zoning of municipal entities and the possibility of their judicial review are due to the requirements to ground the adopted act by the body, as well as the restrictions of the powers of the body that issued the act. In Russia, the mentioned requirements are partly formalized in the legislation, some of them became judicial practice. Generalized judicial practice demonstrates that acts of territorial planning and urban development zoning of municipal entities result from the requirement to justify the adopted city design and the pursuit of the public goal by the body issuing the act. Normal judicial control of such decisions includes evaluation of the act from the point of legality. In some disputes, courts build their arguments based on the principles of legal certainty, proportionality and trust defense.